Diseño De Un Sistema De Información Geográfico Para La Alcaldía Local De Kennedy - Gonzalez Reinoso, Juan Camilo; Leal Gutierrez, Luz Adriana (Universidad Antonio Nariño, 2024)
This study focused on the design and implementation of a Geographic Information System (GIS) for the Kennedy Local Mayor's Office, aiming to enhance the management and distribution of benefits to the community. Utilizing spatial analysis tools and databases, a direct connection was established between the demographic data of the beneficiaries and their specific geographical locations.